PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dewi Ummiyati; Cici’ Insiyah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2021)
The rapid development of the world capital market causes high competition in the business world, not least in the property and real estate business in Indonesia. This certainly encourages every company to continue to compete in improving the company's financial performance in order to attract investors to invest their capital for the company. The property and real estate sector is the most important sector as a driver of the economy in a country. In Indonesia, companies engaged in property and real estate are growing, indicating that the economy is growing in Indonesia. The purpose of this study is to identify and analyze the effect of financial performance on property and real estate stock prices on the Indonesia Stock Exchange. multiple linear regression analysis technique. The type of data used is secondary data. The results of this study indicate that there is a significant positive effect of the financial performance variables Current Ratio (CR), Return on Assets (ROA) and Debt to Equity Ratio (DER) simultaneously on stock prices (Price Earning Ratio (PER) in property companies and real estate listed on the Indonesia Stock Exchange (IDX) for the period 2105-2017 with a significant value of Fcount of 4,603 with a significance level of 0.01 (smaller than significant 0.05) while the value of Ftable is 2.70. This means that the value of Ftable is 2.70. Fcount > Ftable with a value of 4.603 > 2.70 and a sig. level of 0.01 < 0.05, so it can be concluded that the independent variables together have a significant effect on the dependent variable.